Cycle time reduction using lean six sigma in make-to-order (MTO) environment: Conceptual framework - Man, Siti Mariam; Zain, Zakiyah; Mohd Nawawi, Mohd Kamal (2015)
This paper outlines the framework for application of lean six sigma (LSS) methodology to improve semiconductor assembly cycle time in a make-to-order (MTO) business environment.The cycle time reduction is the prime objective in the context of an overall productivity improvement particularly in the MTO environment.The interaction of the production rate and cycle time is described, while the emphasis is on Define-Measure-Analyze-Improve-Control (DMAIC) and Plan-Do-Check-Act (PDCA) activities.A framework for the conceptual understanding is provided along with practical implementation issues. A relevant measure for the degree of flexibility (DOF) in the context of quick setup is also discussed.